Improving nature? : - Reiss, Michael J. (Cambridge University Press, 1996)
Little more than a decade ago the term "genetic engineering" was hardly known outside research laboratories. Today it regularly makes headlines. Those in favor of genetic engineering--and those against it--tell us that it has the potential to change our lives perhaps more than any other scientific or technological advance. But what are the likely consequences of genetic engineering? Is it ethically acceptable? Should we be trying to improve on nature? In Improving Nature?, the authors, a biologist and a moral philosopher, examine the implications of genetic engineering in every aspect of our lives. The underlying science is clearly explained and the moral and ethical considerations are fully disussed, resulting in a wide-ranging, balanced overview of a controversial subject.